BIOLOGY AND NATURAL CONTROL OF Peridroma sama, PEST OF THE FLOWER OF THE PASSION FRUIT - CHACÓN DE ULLOA, PATRICIA; ROJAS DE HERNÁNDEZ, MARTHA (Revista Colombiana de Entomología, 1981)
This paper reports a study on the biology of Peridroma saucia (Hubner) (Lepidoptera, Noctuidae), an insect that causes severe damage, and reduces fruit production of curuba (Passiflora moli (sima). The larval stage feeds on floral parts and it was found that a single individual consumes an average of 2,7 flowers during its development. Sixty percent of the larvae observed were located in the lower part (1/3 from the ground) of the vines. Insects occurred in foci distributed randomly in the field. Population counts were always high during the dry season when 64% of the plants were infested. The duration of the life cycle was affected by temperature and relative humidity. At 8,7°C and 81% RH (natural conditions) it lasted 128 days, while at 20-23°C and 67% RH (laboratory conditions) it was 62,9 days. The sex ratio was 1:1 and the average number of eggs per female 197. Biological control of P. saucia larvae and pupae was also detected. The parasites Incamyia sp (Tachinidae) and Megaselia scalaris (Phoridae), and the predator Anisotarus sp (Carabidae) were frequently observed. Nematodes (Pseudodiplogasteridae) and bacteria, Bacillus cereus, Pseudomonas aeruginosa and Streptococcus sp.